Accuracy analysis of eccentric testing of revolving body based on moment balance principle. Issue 4 (April 2019) - Zhang, Xinming; Shang, Chunmin; Deng, Chunxia; Li, Junye; Chen, Ping; Wang, Xinpeng
Abstract: The eccentricity test of the rotary body has a wide range of applications in aerospace, precision machinery and other fields, using the principle of torque balance, small-range sensors can be used to test the eccentricity of larger quality products, through a small range of the sensor to feel the changes brought about by the lateral force centroid of the rotary body, thereby improving the sensitivity of the test device to measure the transverse centroid, improve test accuracy, eccentricity measurement error caused by random errors and systematic errors, random error is caused by the measurement error of the weighing sensor, system error is caused by inaccurate measurement and inaccurate quality measurement.Through the analysis of the accuracy of the eccentricity test, the accuracy of the eccentricity test can be controlled within 0.005 mm.